The Connection Between the Sufi Curriculum and Character Education of Santri Dayah in Aceh - Daniel, Muhammad; Subita, Aulia; Mukhtar, Kamal; Hidayatullah, Muhammad Fahmi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research aims to explore how the Sufi curriculum at Dayah Mudi Mesra influences the spiritual development and character of the students (santri). Utilizing a qualitative research method with a case study approach, data were collected through in-depth interviews, observations, and documentation, involving both santri and teachers at the dayah. An interactive analysis method by Miles and Huberman was applied to interpret the data, which was validated using triangulation techniques. The findings indicate that the Sufi curriculum, which emphasizes the teaching of classical texts such as Ihya Ulumuddin, as well as daily practices like dhikr (remembrance of God) and wirid (recitations), is effective in shaping the character of the santri. Values such as religiosity, honesty, and responsibility have become internalized in the daily lives of the santri, strengthening their spiritual connection with Allah SWT and their discipline in worship. However, the main challenges include a lack of resources, particularly a shortage of trained instructors in Sufism, and limited supporting facilities. This research fills a gap in the literature by connecting the Sufi curriculum with character education and provides recommendations for other institutions seeking to integrate Sufism into character education. It is recommended that training be provided for teachers to enhance their understanding and teaching skills in Sufism, as well as to increase social activities to boost the engagement of santri within the community. Overall, this research contributes not only to academic discourse but also offers practical guidance for developing a more holistic model of Islamic education that can be implemented in other institutions.